Teacher Obstacles in the Scientific Approach to Thematic Learning in Class III SD Negeri 2 Jeumpet Aceh Besar - maghfirah, ira; Mislinawati, Mislinawati; Yamin, M. (Elementary Education Research, 2023)
The purpose of this study was to find out how the teacher's obstacles and the application of a scientific approach to thematic learning in class III SD Negeri 2 Jeumpet Aceh Besar. In this study, the formulation of the problem is how to apply and the teacher's obstacles in applying the scientific approach to thematic learning in class III. This study used a qualitative approach with a descriptive research type. The subjects in the study were 1 teacher, namely a class III teacher at SDN 2 Jeumpet Aceh Besar. Data collection techniques through in-class observation and interviews. Data analysis namely data reduction, data presentation, and drawing conclusions. The results of the analysis of observation and interview data in class III teachers apply a scientific approach to thematic learning properly according to the steps that must be taken. so that it has an impact on the student's ability to find himself. Obstacles in the scientific approach are more external factors, namely students are still less active in observing, asking, reasoning, trying, associating and communicating in class III SDN 2 Jeumpet relatively low, this has an impact on the final process expected to find their own concepts or principles in learning thematic does not occur, which requires the activeness of the students not the activeness of the teacher. Suggestions to teachers to continue implementing better strategies to increase student activity in class.